Неогеновый прокобус Западного Причерноморья - Короткевич, Е.Л.; Крахмальная, Т.В. (Вестник зоологии, 1983)
A description of two incomplete cranium specimens of an extinct goat, Procobus melania, from Macotic deposits of Tarakliya (Moldavia) and Novaya Emetovka (Ukraine). The new finds permit elucidating the neural part of the cranium structure, thus giving an additional material for the generic diagnosis. primary compiled on the basis of horn stiits and dentition. The presence of P. melania, formerly known only from Moldavia, in the Hipparion fauna of the Ukraine, extends its range and suggests paleogeographic conditions within the area under study.